Examining Performance of Geometrical Thinking in Mathematics at Secondary School Level in Pakistan - Amir Zaman, Abdul Ghafar, Fazal ur Rahman, Ishtiaq Hussain (PJE, 2023)
Geometrical thinking is important for students to perform well in mathematics as a whole. This study aimed at assessing performance of grade 9th students in Geometrical thinking. Furthermore, comparison among students in different strata was made like sector wise, gender wise and location wise. A test of reasoning was administered to a sample of above 500 hundred. Sample of the study was taken with proportionate approach from the whole population. The test was properly validated and reliably checked using SPSS. Factor analysis of the test shows that all items were statistically aligned with theoretical model. The results show that the students perform in a variety of ways like performance of private schools students was significantly better than students of public schools. Similarly, male and urban students performed well than female and rural students respectively. However, the difference between score of the students in private and public schools were found significant. Interaction analysis of gender, rural urban divide shows; that some items show interaction effect by behaving differently in response to background variables. It was recommended for further research to replicated this study on different level with tools suitable for their level and also can be better conducted using tools that involve diagrammatic reasoning.